Analysis of Potential and Feasibility of Hydropower Energy from Sepaku Semoi Dam in Penajam Paser Utara Regency. Issue 1 (December 2021) - Nashrulloh, Faruq; Sulaiman, Muhammad; Budiarto, Rachmawan
Abstract: This paper will present a techno-economic potential and feasibility analysis in the planning of renewable hydropower energy from Sepaku Semoi Dam in Penajam Paser Utara (PPU) Regency. The dam was planned to be built to support the water needs of Indonesia's prospective capital. The analysis was done based on the last twenty years' rainfall intensity data history from Sepaku rain station and Sepinggan rain station and digital elevation model (DEM) from DEMNAS with support of the river basin agency of Kalimantan Timur. The result of dependable discharge calculation of Sepaku Semoi river using FJ Mock Method is 2.45 m/s 2 . And the head of the hydropower power plant is 15.85 meters. The total potential electricity generated from hydropower reached 2, 593, 140 kWh/year. The assessment of feasibility indicators in this research took into account the technology and economic aspects. The technology aspects help evaluate the technical planning of installations that are possible to build in the dam. The economic aspect of feasibility evaluates the net present value (NPV), internal rate of return (IRR), and the payback period of renewable energy installation. This analysis aimed to get a comprehensive insight from the potential hydropower energy that exists at the research locations and conduct a feasibility study based on techno-economic analysis to develop renewable energy. The results showed that 15.85 meters had the most significant potential of hydropower by generating 290 kW continuous power with a feed-in tariff of 0.054 USD/kWh. The electricity was feasible to offer to the government electrical company. Moreover, this project had a payback period of 8 years, and NPV of 64, 005 USD, and an IRR Project of 11.86%.